Evaluasi Jejak Karbon pada Produksi Black Garlic Sembalun menggunakan Pendekatan Penilaian Daur Hidup (Life Cycle Assessment) - Joni Safaat Adiansyah; Fathul Rakhman; Mustiana (Al-Ard: Jurnal Teknik Lingkungan, 2023)
Abstract Sembalun is well known as one of tourism destination in Lombok Island with main attraction is Rinjani Mountain hiking. Currently, there are also some other tourism attractions such as hill climbing, garden and fruit tours, and photo spots. In addition, many people come to spend their weekend in Sembalun. The increase in the number of tourist visits to Sembalun is an opportunity to develop various Sembalun souvenirs. One of them is Sembalun black garlic. Black Garlic Sembalun uses garlic as a raw material. The purpose of this study is to estimate the carbon footprint of Sembalun black garlic production where the method used is a Life Cycle Assessment. The unit function used is the production of black garlic in a month. A case study was taken from the UMKM KWT Putri Rinjani in Sembalun Bumbung Village which produces black garlic. There are five stages in the black garlic production process, namely transportation, drying, peeling, roasting, and packaging. From the results of the analysis using the OpenLCA software, three process stages contributed to the carbon footprint of Sembalun black garlic production, namely the transportation stage (52.125 KgCO2eq), the roasting stage (46.707 KgCO2eq), and the packaging process (6.930 KgCO2eq). To reduce the carbon footprint, several sustainable improvement alternatives that can be carried out include storing (stock) raw material to reduce the number of transportation trip and using transportation vehicles that have better combustion efficiency and the use of electric vehicles. Keywords: carbon footprint, black garlic, transporting, roasting, packaging.